2006
DOI: 10.1073/pnas.0602382103
|View full text |Cite
|
Sign up to set email alerts
|

Transferable anticancer innate immunity in spontaneous regression/complete resistance mice

Abstract: Spontaneous regression͞complete resistance (SR͞CR) mice resist very high doses of cancer cells that are lethal to WT mice even at low doses. In this study, we show that this resistance is mediated by rapid infiltration of leukocytes, mostly of innate immunity, in both primary and repeated challenges. Formation of rosettes with infiltrating natural killer cells, neutrophils, and macrophages was required for the subsequent destruction of cancer cells through rapid cytolysis. Highly purified natural killer cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
124
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 18 publications
11
124
2
1
Order By: Relevance
“…TLRs are primary drivers of innate immunity, and there is increasing evidence that innate cells such as macrophages and neutrophils have potent antitumour effects. This has most recently been seen in a study by Hicks et al (2006), who have demonstrated that the basis for complete tumour resistance in the spontaneous regression/complete resistance mouse is due to innate cells whose antitumour effect can be adoptively transferred to recipient mice. Cancer researchers investigating antitumour immunity are colloquially referring to the Toll-like receptors in cancer LAJ O'Neill donor mouse as the 'wonder mouse' (J Obijeski, personal communication), and there is a strong likelihood that TLRs are involved in this process.…”
Section: Toll-like Receptors In Cancer Laj O'neillmentioning
confidence: 90%
“…TLRs are primary drivers of innate immunity, and there is increasing evidence that innate cells such as macrophages and neutrophils have potent antitumour effects. This has most recently been seen in a study by Hicks et al (2006), who have demonstrated that the basis for complete tumour resistance in the spontaneous regression/complete resistance mouse is due to innate cells whose antitumour effect can be adoptively transferred to recipient mice. Cancer researchers investigating antitumour immunity are colloquially referring to the Toll-like receptors in cancer LAJ O'Neill donor mouse as the 'wonder mouse' (J Obijeski, personal communication), and there is a strong likelihood that TLRs are involved in this process.…”
Section: Toll-like Receptors In Cancer Laj O'neillmentioning
confidence: 90%
“…A spontaneously arising sarcoma was found to be transmissible among a colony of Syrian hamsters (Brindley and Banfield, 1961;Cooper et al, 1964), and this cancer could even be experimentally transferred between individuals by mosquitoes (Banfield et al, 1965). A number of mouse cancer cell lines can be propagated by intraperitoneal injection through unrelated mouse strains (Carry et al, 1979;Hicks et al, 2006). Transmissible cancers with unknown etiology, some of which are transplantable, have been described in newts and fish (Champy and Champy, 1935;Lucke and Schlumberger, 1949).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the inhibition of MyD88 promoted the tumor progression. In the previous study, infiltrating inflammatory cells, such as neutrophils and macrophages, could destroy cancer cells by rapid cytolysis (Hicks et al, 2006). Furthermore, neutrophils also showed antituomor effects in several types of cancer models (Challacombe et al, 2006;Nozawa et al, 2006).…”
Section: Discussionmentioning
confidence: 89%